1993
DOI: 10.1111/j.1365-2621.1993.tb06115.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere Packaging Protects Market Quality in Broccoli Spears Under Ambient Temperature Storage

Abstract: Broccoli spears were packaged using a semipermeable polymeric film and stored 96 hr at 20°C. COa and O2 concentrations within the packages equilibrated to about 9 and 3%, respectively. Relative to nonpackaged spears, ascorbic acid, chlorophyll and moisture retention were greater; and peroxidase activity was lower in packaged broccoli. No differences were found in total aerobic microbial population growth or Instron shear values between packaged and control spears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
11

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 9 publications
2
24
0
11
Order By: Relevance
“…[3][4][5] Refrigeration in combination with modified atmosphere packaging (MAP) or vacuum packaging (VP) is being employed as a mild preservation technique to ensure safety, quality and shelf-life extension of many minimally processed fresh (MPF) vegetables. 2,6 However, inhibition of spoilage flora by modified atmosphere packaging of ready-to-eat vegetables may result in survival and/or growth of pathogens, 1,7,8 which is facilitated by the lack of natural competitors and the increased time available for growth. 1 Additionally, the low and negligible levels of oxygen in modified atmosphere and vacuum packaging respectively could enable growth and toxin production by Clostridium botulinum.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Refrigeration in combination with modified atmosphere packaging (MAP) or vacuum packaging (VP) is being employed as a mild preservation technique to ensure safety, quality and shelf-life extension of many minimally processed fresh (MPF) vegetables. 2,6 However, inhibition of spoilage flora by modified atmosphere packaging of ready-to-eat vegetables may result in survival and/or growth of pathogens, 1,7,8 which is facilitated by the lack of natural competitors and the increased time available for growth. 1 Additionally, the low and negligible levels of oxygen in modified atmosphere and vacuum packaging respectively could enable growth and toxin production by Clostridium botulinum.…”
Section: Introductionmentioning
confidence: 99%
“…2). CA or MA has been shown to delay the yellowing of broccoli florefs stored at 4'C (Bastrash et al, 1993), lO'C (Barth et al, 1993a), 15'C (Hirata et a/, 1995), 20'C (Barth et al, 1993b;Abe et al, 1995), and 25'C (Makhlouf et al, 1989b). Abe et al ( 1995) reported that ethyl alcohol or acetaldehyde delayed yellowing and decreased ethylene production of broccoli fiorets as well as a high C02 atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Volatile sulfur compounds were not detected in the headspace of the package (Table 1). Barth et al 1 reported that storage of broccoli under 9% CO 2 and 3% O 2 resulted in better maintenance of quality. In this experiment, storing the packaged broccoli at 10ºC must have favorably modified the atmosphere condition inside the package.…”
Section: Resultsmentioning
confidence: 99%